NEW INSIGHTS INTO THE PRESENCE OF BILIRUBIN IN A PLANT SPECIES STRELITZIA NICOLAI (STRELITZIACEAE). - Dwarka, Depika; Thaver, Veneesha; Naidu, Mickey; Baijnath, Himansu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The fortuitous discovery of an animal pigment bilirubin found in the plant Strelitzia nicolai has openedan enormous number of questions regarding bilirubin’s formation and its ultimate function in the human body.Materials and Methods: A methodical review of bilirubin in humans and animals was carried out, information wasgathered using published scientific journals, books and conference proceedings. Articles based on case studies ofelevated levels of bilirubin were analysed thoroughly.Results: Even though for numerous years bilirubin was assumed to be merely a desecrate product of the heme catabolicpathway by greatest, and a likely lethal compound at worst; statistics from the last few decades clearly shows thatplacidly high serum bilirubin levels are robustly related to have abundant beneficial effects on the human body.Conclusion: This study reveals new insights into the presence of the only animal pigment found in Strelitzia nicolaiarils, the potential advantages of bilirubin found in a plant and its therapeutic value indications. This review hopes toresuscitate researchers’ credence regarding bilirubin as a toxic compound.